Clinical and economic burden associated with symptomatic and asymptomatic obstructive hypertrophic cardiomyopathy in Germany - Sedaghat-Hamedani, Farbod; Zema, Carla L.; Schultze, Michael; Garcia, Tarcyane B.; Kossack, Nils; Borchert, Julia; Maksabedian Hernandez, Ervant J.; Zhong, Yue; Bluhmki, Tobias; Krause, Taryn; Schmoelders, Johanna; Meder, Benjamin (Clinical research in cardiology, 2025)
Background: The clinical and economic burden of obstructive hypertrophic cardiomyopathy (HCM) in Germany for symptomatic versus asymptomatic patients has not been comprehensively assessed. Methods: This retrospective observational study analyzed nationally representative WIG2 Benchmark Database data, identifying adults diagnosed with obstructive HCM from 2012 to 2018. Study index was the first date when a participant met eligibility criteria. An algorithm based on coded symptoms and pharmacological treatments was used to divide patients into symptomatic and asymptomatic subgroups. Annual prevalence, patient characteristics, outcomes, resource utilization, and costs were assessed during follow-up. Results: Overall, 1141 patients were included (649 symptomatic patients and 492 asymptomatic patients during the 1-year pre-index period [baseline]). In total, 1042 patients had symptomatic disease at some point during follow-up. Annual obstructive HCM prevalence increased between 2011 and 2019 and was higher for symptomatic than asymptomatic patients. Compared with asymptomatic patients, symptomatic patients: were older (mean age: 62.8 vs. 55.5 years), were less likely to be male (59% vs. 67%), and had higher Charlson Comorbidity Index (mean: 2.82 vs. 1.69) at baseline; had higher rates of all-cause mortality (0.05 vs. 0.02 per 100 patient-years) and cardiovascular events (mean follow-up: 4.7 years); had more outpatient visits (13.3 vs. 10.8 per patient-year [PPY]), inpatient visits (0.7 vs. 0.5 PPY), and longer mean length of stay (8.7 vs. 7.4 days); and had higher mean costs PPY for outpatient, inpatient, and pharmacy services (total: €5975 vs. €4399).Conclusions: Patients with symptomatic obstructive HCM experienced greater clinical and economic burden than asymptomatic patients in Germany.